Arterial Stiffness and Chronic Kidney Disease Progression in Children. Issue 10 (October 2022) - Azukaitis, Karolis; Kirchner, Marietta; Doyon, Anke; Litwin, Mieczysław; Bayazit, Aysun; Duzova, Ali; Canpolat, Nur; Jankauskiene, Augustina; Shroff, Rukshana; Melk, Anette; Querfeld, Uwe; Schaefer, Franz
Visual Abstract: Abstract : Background and objectives: CKD has been linked to increased arterial stiffness in adults, but data in children with CKD remain conflicting. We aimed to investigate the longitudinal dynamics and determinants of pulse wave velocity in children with CKD and its association with CKD progression. Design, setting, participants, & measurements: We performed an analysis of the Cardiovascular Comorbidity in Children with Chronic Kidney Disease (4C) study, which prospectively followed children aged 6–17 years with CKD stages 3–5. Follow-up was censored at the time of KRT initiation. Two separate analyses were performed: with absolute pulse wave velocity (primary outcome) and with pulse wave velocity standardized to height ( z score; restricted to participants ≤17 years) as a sensitivity analysis. Results: In total, 667 patients with a mean baseline eGFR of 27 ml/min per 1.73 m 2 were included. Pulse wave velocity above the 95th percentile was observed in 124 (20%) patients at baseline. Absolute pulse wave velocity increased gradually over the median follow-up of 2.7 (interquartile range, 0.7–4.4) years, whereas pulse wave velocity z score remained relatively stable. Absolute pulse wave velocity over time associated with time; older age; higher mean arterial pressure, LDL cholesterol, and albuminuria; and lower ferritin. Pulse wave velocity z score ( n =628) was associated with the same variables and additionally, with higher diastolic BP z score, lower height z score, younger age, and girls. Of 628 patients, 369 reached the composite end point of CKD progression (50% eGFR loss, eGFR <10 ml/min per 1.73 m 2, or the start of KRT) during a median follow-up of 2.4 (interquartile range, 0.9–4.6) years. Pulse wave velocity z score did not associate with CKD progression by univariable or multivariable proportional hazard analysis correcting for the established predictors eGFR, proteinuria, and BP. Conclusions: Pulse wave velocity is increased in children with CKD but does not associate with eGFR or CKD progression.